Assessing cardiac and liver iron overload in chronically transfused patients with sickle cell disease. (10th August 2016) - Badawy, Sherif M.; Liem, Robert I.; Rigsby, Cynthia K.; Labotka, Richard J.; DeFreitas, R. Andrew; Thompson, Alexis A.
Summary: Transfusional iron overload represents a substantial challenge in the management of patients with sickle cell disease (SCD) who receive chronic or episodic red blood cell transfusions. Iron‐induced cardiomyopathy is a leading cause of death in other chronically transfused populations but rarely seen in SCD. Study objectives were to: (i) examine the extent of myocardial and hepatic siderosis using magnetic resonance imaging (MRI) in chronically transfused SCD patients, and (ii) evaluate the relationship between long‐term (over the 5 years prior to enrolment) mean serum ferritin (MSF), spot‐ferritin values and liver iron content (LIC) measured using MRI and liver biopsy. Thirty‐two SCD patients (median age 15 years) with transfusional iron overload were recruited from two U.S. institutions. Long‐term MSF and spot‐ferritin values significantly correlated with LIC by MRI‐R2* ( r = 0·77, P < 0·001; r = 0·82, P < 0·001, respectively). LIC by MRI‐R2* had strong positive correlation with LIC by liver biopsy ( r = 0·98, P < 0·001) but modest inverse correlation with cardiac MRI‐T2* ( r = −0·41, P = 0·02). Moderate to severe transfusional iron overload in SCD was not associated with aberrations in other measures of cardiac function based on echocardiogram or serum biomarkers. Our results suggest that SCD patients receiving chronic transfusions may not demonstrate significant cardiac iron loading irrespective of ferritin trends, LIC and erythropoiesis suppression.